Analisis Peran Hati Nurani dalam Surat-surat Paulus dan Etika Kristen - Bambang Subandrijo (Theologia in Loco, 2020)
This article explores the meaning of conscience (sunedēsis) in the Pauline letters in relation to Christian ethics. I have argued that if humans act based on their conscience, without depending on the judgment of others, they will be their own self. Obedience to conscience is an ethical egoism that starts from conscience, because its ethical actions are rooted in moral truth which becomes a moral obligation. The understanding of conscience in the Pauline letters show that decision making does not depend on others, but depends on conscious personal decisions. By doing so, someone appears as him or herself who has a strong personality and a great-hearted person. By taking a decision based on conscience, man will act carefully, prudently and be conscious to take responsibility for his or her actions.